Characterizing the Severity of SARS-CoV-2 Variants at a Single Pediatric Center - Khan, Aslam; Ichura, Caroline; Wang, Hannah; Rezende, Izabela; Sahoo, Malaya K.; Huang, ChunHong; Solis, Daniel; Sibai, Mamdouh; Yamamoto, Fumiko; Nyathi, Sindiso; Bayrau, Bethel; Pinsky, Benjamin A.; et al. (Frontiers in Medicine, 2022)
Since March 2020, SARS-CoV-2 has plagued the world with COVID-19 and individuals of all ages have experienced varying symptoms of disease. Older adults were experiencing more severe disease compared to children and were prioritized by vaccination efforts. While biologic therapies and vaccinations were implemented, there were changes in public health restrictions with subsequent surges resulting in more infected children. During these surges there was a rise of different SARS-CoV-2 variants with the dominant variant initially alpha (B.1.1.7 and other Pango lineages) and epsilon (B.1.427/B.1.429) in early 2021 and a dramatic shift to delta (B.1.617.2 and other Pango lineages) by mid-summer 2021. In this study we aimed to characterize the clinical severity and host factors associated with disease by SARS-CoV-2 variant and evaluate if there are differences in disease severity by circulating variant. We retrospectively included all individuals 0–25 years of age who presented to our center and had a positive SARS-CoV-2 RT-PCR, SARS-CoV-2 variant mutation testing, and documented clinical notes from 1 January 2021 through 31 December 2021. We identified 745 individuals who met inclusion criteria and found the delta variant was associated with severe/critical disease compared to the other variants studied. The results of the model showed that underlying respiratory disease and diabetes were risk factors for progression to severe disease. These insights are important when evaluating public health measures and treatment options for children as more variants arise.